Comic-film-music of “Pendekar Cyborg”: a case study of transmedia storytelling in Indonesian contemporary independent comics - Bajraghosa, Terra; Irawanto, Budi; Ajidarma, Seno Gumira (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
This study explores independently published comics in Indonesia after 2010, which show differences from independent comics in the late 1990s and early 2000s. Contemporary independent comics distinguish themselves by positioning readers as patrons and the application of transmedia storytelling across platforms, especially related to film and music, and not for industrial purposes. The research questions presented are: what are transmedia storytelling practices in contemporary independent comics in Indonesia, and how is the context of creative freedom and control that underlies the production of printed comics presented through cross-media platforms? Using qualitative methodology, this study applies descriptive discourse analysis based on the visual culture framework, following Gillian Rose's methodological approach. The descriptive analysis focuses on the case study of transmedia storytelling